A Prototype Model of Monitoring Energy Consumption and Optimizing Distribution of Smart Buildings - Shalaby A.M.; Sidhu M.S.; Tan W.C.; Wei L.Z.; Yong C.J.; Xi L.Y. (Institute of Electrical and Electronics Engineers Inc., 2023)
Education computing; Energy utilization; Intelligent buildings; Internet of things; Long short-term memory; Open systems; Particle swarm optimization (PSO); Remote control; Arduino; Firebase; Firestore; LSTM; MQTT broker; Neural-networks; Opencv; PSO; Raspberry PI; Weather API; Python